# 3(2+x)-5(x-2)=x-2(3-x)

## Simple and best practice solution for 3(2+x)-5(x-2)=x-2(3-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 3(2+x)-5(x-2)=x-2(3-x) equation:

3(2+x)-5(x-2)=x-2(3-x)
We move all terms to the left:
3(2+x)-5(x-2)-(x-2(3-x))=0
We add all the numbers together, and all the variables
3(x+2)-5(x-2)-(x-2(-1x+3))=0
We multiply parentheses
3x-5x-(x-2(-1x+3))+6+10=0

We calculate terms in parentheses: -(x-2(-1x+3)), so:
x-2(-1x+3)
We multiply parentheses
x+2x-6
We add all the numbers together, and all the variables
3x-6
Back to the equation:
-(3x-6)

We add all the numbers together, and all the variables
-2x-(3x-6)+16=0
We get rid of parentheses
-2x-3x+6+16=0
We add all the numbers together, and all the variables
-5x+22=0
We move all terms containing x to the left, all other terms to the right
-5x=-22
x=-22/-5
x=4+2/5

`